2020
DOI: 10.31533/pubvet.v14n6a594.1-9
|View full text |Cite
|
Sign up to set email alerts
|

Estudo retrospectivo da tuberculose bovina no estado do Maranhão: 2013 a 2018

Abstract: Resumo.A tuberculose bovina é uma doença de caráter mundial. Sendo uma das principais zoonoses identificadas em abatedouros frigoríficos. As perdas econômicas estão relacionadas à baixa produtividade, queda na conversão alimentar, reprodução e à condenação de carcaças em matadouros, por isso, os métodos de controle desta enfermidade no Brasil são definidos pelas normativas do Programa Nacional de Controle e Erradicação da Brucelose e da Tuberculose Animal (PNCEBT), instituído em 2001 pelo Ministério da Agricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The lower number of infections in males may be related to the fact that these animals are isolated from other animals for most of the year, making it possible to identify a higher proportion of infected bulls when compared to young animals [ 25 ]. In a study carried out by Oliveira et al [ 26 ] a prevalence of 0.003% was identified in the carcasses of cattle affected by tuberculosis in the state of Maranhão. Lopez et al [ 27 ] identified a prevalence of 0.00087% in the state of Rondônia due to tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…The lower number of infections in males may be related to the fact that these animals are isolated from other animals for most of the year, making it possible to identify a higher proportion of infected bulls when compared to young animals [ 25 ]. In a study carried out by Oliveira et al [ 26 ] a prevalence of 0.003% was identified in the carcasses of cattle affected by tuberculosis in the state of Maranhão. Lopez et al [ 27 ] identified a prevalence of 0.00087% in the state of Rondônia due to tuberculosis.…”
Section: Discussionmentioning
confidence: 99%